2007
DOI: 10.1097/01.iae.0000221996.77421.69
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Vitrectomy With or Without Arteriovenous Sheathotomy in Branch Retinal Vein Occlusion

Abstract: Our findings suggest that vitrectomy with or without arteriovenous sheathotomy may improve the long-term functional and tomographic outcomes for patients with macular edema secondary to BRVO. Although additional arteriovenous sheathotomy did not lead to a distinct functional benefit in this series, early surgical intervention may result in better visual outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 23 publications
(29 reference statements)
2
35
0
5
Order By: Relevance
“…In addition, Saika et al [8] reported that vitrectomy combined with surgical posterior vitreous detachment was effective for macular edema in BRVO patients. Moreover, it has been reported that macular edema and visual acuity can be improved in patients with BRVO by this procedure [9,10]. Accordingly, we performed vitrectomy more than 3 months after the onset of BRVO in patients with CME.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Saika et al [8] reported that vitrectomy combined with surgical posterior vitreous detachment was effective for macular edema in BRVO patients. Moreover, it has been reported that macular edema and visual acuity can be improved in patients with BRVO by this procedure [9,10]. Accordingly, we performed vitrectomy more than 3 months after the onset of BRVO in patients with CME.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, PPV reduces the intraocular levels of various other inflammatory factors in addition to VEGF, 30 and this may be another mechanism by which it alleviates macular edema in patients with BRVO. In fact, it has been reported 31,32 that PPV improves both functional and tomographic outcomes in patients with BRVO and macular edema. Accordingly, we performed PPV in patients with clinically detectable diffuse macular edema or cystoid macular edema more than 3 months after the onset of BRVO.…”
Section: Participantsmentioning
confidence: 99%
“…Peeling of the ILM may be reserved for clinical situations in which other modalities of treatment, namely the intravitreal injection of antiedematous (steroids) or anti-VEGF drugs, have failed to achieve a satisfactory improvement in vision, and in which the blood perfusion of the macula physiologically allows an increase in VA [112,131,133,134,135,136,137,138,139,140,141]. …”
Section: Surgical Approaches To Treating Rvomentioning
confidence: 99%